Improving the Welfare of Honorary Teachers Through the Implementation of Pentahelix in Stakeholders in the Scope of Education - Purwandani, Anna; Qomariyatus Sholihah; Mochammad Rozikin (Universitas Pendidikan Ganesha, 2024)
The welfare of honorary teachers in Elementary Schools is still relatively low, mainly because the wages are far below standard. Although BOS funds of 15% of IDR 342,000,000 per year have been allocated, this amount is not enough to meet the needs of honorary teachers. Limited resources worsen the situation and hinder the effectiveness of collaboration in improving their welfare. This study aims to analyze the improvement of honorary teacher welfare through implementing Pentahelix in education sector stakeholders. This study uses a descriptive qualitative method, and data analysis is carried out using the Miles, Huberman, and Saldana methods. Data were collected through observation, interviews, and documentation from 10 informants. The results show that collaboration between the Education Office, principals, school committees, cooperatives, and social media is key, with the most significant contribution from the Education Office (40%). However, coordination and resources need to be improved for the effectiveness of this model. The implications of the results of this study are a deeper understanding of the role of each stakeholder in supporting the welfare of honorary teachers, mainly how policies from the Education Office contribute significantly.